Dikotomi Pendekatan dalam Kajian Ilmu Hukum: Sebuah Tinjauan Kritis - Nurul Qamar; Farah Syah Rezah (CV. Social Politic Genius (SIGn), 2022)
This study aims to examine and analyze the dichotomy between doctrinal and non-doctrinal approaches in the study of legal science. This research uses normative research methods. The collection of legal materials is done by using literature study techniques. The legal material obtained in this study was then analyzed qualitatively with a comparative approach to present conclusions and answer the research objectives. The results show that the dichotomy of approach in the study of legal science is a scientific dynamic in line with social changes in the community. The doctrinal approach is a normative legal study that always focuses on norms that are none other than the character of legal science itself. In contrast, the non-doctrinal approach is an empirical legal study that crosses other scientific disciplines and does not ignore legal norms as the character of legal science. In addition, the doctrinal approach determines substantially what is allowed and what is not (das sollen). At the same time, the non-doctrinal approach corrects legal behavior as nothing but a judiciary that creates justice, certainty, and utility in the empirical realm (das sein). Therefore, it is recommended for legal academics to have progressive legal thought construction. In addition, the government must ensure every legal academic’s competence when making academic manuscripts of Laws and Regulations Draft. In this case, the rule of law must achieve social justice for Indonesia’s people.